SISTEM INFORMASI GAJI KARYAWAN MENGGUNAKAN FRAMEWOK CODEIGNITER - Dadi Rosadi; Wulandari Wulandari (Jurnal Computech & Bisnis (e-Journal), 2020)
CV. Davina23 is a company engaged in the provision of goods and services. Where in the company there are problems that will be faced, namely the addition of new employees, the process of calculating employee salaries, data collection and recording of attendance are still done semi-computer, using Microsoft Excel. Given the weaknesses in recruiting new employees, absences, calculating salaries and preparing reports, a study was conducted to design a payroll information system in overcoming existing problems. The research method used is descriptive method. The research was conducted by conducting a direct review on the CV. Davina23. By using the Codeigniter Framework, it is hoped that it is easy to understand, it can make it easier to process employee salary data in more complete and detail. The design of this information system is carried out using an object-oriented methodology (OOSE), which consists of Use Case Diagrams, Use Case Scenarios, Activity Diagrams, Class Diagrams, and Sequence Diagrams. The resulting application design functions to perform processing, transaction processing, and report generation. With a computerized information system, information is processed more quickly and calculations can be performed more precisely and accurately. Keywords: system information, salary, employees, framework codeigniterDOI : http://doi.org/10.5281/zenodo.4320258